2015
DOI: 10.2967/jnumed.114.143164
|View full text |Cite
|
Sign up to set email alerts
|

SPECT Myocardial Perfusion Reserve in Patients with Multivessel Coronary Disease: Correlation with Angiographic Findings and Invasive Fractional Flow Reserve Measurements

Abstract: Quantification of myocardial perfusion reserve (MPR) is an emerging topic in nuclear cardiology with an expected diagnostic and prognostic incremental value, especially for patients with severe coronary artery disease. The advent of new dedicated solid-state cameras has opened new perspectives for perfusion quantitation in SPECT. We appraised the feasibility of perfusion reserve estimation using a cadmium zinc telluride camera in a cohort of multivessel patients and its pertinence with respect to angiographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 33 publications
2
77
1
4
Order By: Relevance
“…We compared the global mean MFR of 1 vessel disease to those of 2-3 vessel disease patients. The MFR of 1 vessel disease patients was significantly higher than that of multi vessel disease, which was compatible with earlier studies (12,20). In this study, 10 of the CAD group (n=25) had a history of CABG, and 5 of the CAD group had a history of myocardial infarction with fixed perfusion defects in the SPECT, which may affect significantly to the MFR values and complicated the results.…”
Section: Discussionsupporting
confidence: 80%
“…We compared the global mean MFR of 1 vessel disease to those of 2-3 vessel disease patients. The MFR of 1 vessel disease patients was significantly higher than that of multi vessel disease, which was compatible with earlier studies (12,20). In this study, 10 of the CAD group (n=25) had a history of CABG, and 5 of the CAD group had a history of myocardial infarction with fixed perfusion defects in the SPECT, which may affect significantly to the MFR values and complicated the results.…”
Section: Discussionsupporting
confidence: 80%
“…16 Both global and regional MPR correlated with angiographic coronary stenosis and invasive FFR among patients with multivessel coronary artery disease. 17 Combining dynamic CZT-SPECT imaging with CT attenuation correction allows assessment of absolute MBF and MFR. In a porcine model, Wells et al 18 demonstrated the feasibility of MBF assessment using a dedicated cardiac CZT camera and CT-based attenuation and scatter correction.…”
Section: Dynamic Spect Imagingmentioning
confidence: 99%
“…19 Another PET-like quality, recently attributed to CZT-MPI is the feasibility to perform dynamic tomographic imaging, and quantify a myocardial perfusion reserve index, representing the ratio of peak myocardial blood flow to resting myocardial blood flow. 20,21 This measurement has the potential to increase the sensitivity of MPI in detecting extensive CAD when relative perfusion is normal due to balanced hypoperfusion, and reduced flow heterogeneity. A new PET-like performance of CZT technology is shown in the present study by Brodov et al, demonstrating the feasibility of measuring the EF reserve by short, successive acquisitions, starting 5 minutes after regadenoson injection, and detecting a negative, early EF reserve among ischemic patients, compared to a positive EF reserve among nonischemic patients.…”
mentioning
confidence: 99%